46 ATORVASTATIN ATTENUATES VASCULAR GLOMERULI ATHEROSCLEROSIS IN EXPERIMENTAL HYPERCHOLESTEROLEMIA. (1st March 2005) - Gallagher, P.; Le, T. A.; Pandya, S.; McConnell, J.; Singh, R.; Caira, F.; Gocek, J.; Subramaniam, M.; Spelsberg, T. C.; Rajamannan, N. M.
Abstract : Background: Recent studies link early renal insufficiency to increased cardiovascular risk factors. Chronic renal nephrosclerosis is a common cause for end stage renal disease and an indication for hemodialysis. We studied a model of experimental hypercholesterolemia with and without atorvastatin to determine the cellular mechanisms of nephrosclerosis. Methods: 48 Watanabe rabbits were assigned to one of three groups: cholesterol (1% diet), cholesterol (1% diet) plus atorvastatin (2.5 mg/kg), and normal diet (control) for six months. The kidneys were studied and serum creatine levels were measured. Electron microscopy, immunohistologic staining and Western blots were performed. The following atherosclerotic markers were tested, including macrophage (RAM-11), α-actin smooth muscle, and proliferating nuclear cell antigen (PCNA). Bone matrix expression was determined by Western blot for osteopontin and osteocalcin. Results: Serum creatine levels (0.9 ± 0.03 mg/dL control vs. 1.3 ± 0.43 mg/dL cholesterol, p<0.05) macrophage, α-actin, osteopontin, osteocalcin and PCNA were increased in the vascular glomeruli from the cholesterol-treated rabbits. Atorvastatin decreased the amount of atherosclerosis, proliferation and bone matrix protein expression with no significant change in the serum creatinine levels (1.12 ± 0.25) in these treated kidneys. Conclusion: Experimental hypercholesterolemia induces proliferation and osteopontin expression in the glomeruli that may potentially be modified with the use of a lipid-lowering agent.